(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
In the pandemic context several specificities should be underlined for the case of vaccine trials, in addition to all ethical concerns raised for research related to pharmacological treatments which are also valid for vaccine research. Study population in vaccine trials is built up with healthy volunteers that should be carefully and fairly selected; as far as vaccine for emergency use are approved, the use of placebo in controlled studies raises ethical questions that should be discussed. Participants in vaccine trials should in any case be unduly influenced by any form of payment, and the gratuity of their act should be stressed in the communication and consent process. Moreover, in the context of experimentation with vaccines, sensitive ethical issues can arise also from the so-called "challenge studies", since they concern intentionally infecting healthy people to investigate diseases and their treatments (human challenge trials involve exposing healthy volunteers to a pathogen to learn more about the disease it causes and to test vaccines quickly). The contribution finally includes a specific list of aspects to be included in well-designed information and consent process for participants’ in vaccine research in the Covid-19 pandemic.